Efficiency improvement of antenna testing based on diversity technology - Shaogeng AN; Yuliang FANG; Lin CHEN (Dianxin kexue)
With the development of mobile communication，the efficiency of the antenna test demand is higher and higher，but antenna test efficiency is subject to the testing principle.In order to improve the test efficiency while ensuring accuracy of test results，the concept of diversity test was introduced.After argument and research，the test system was reformed.The test results show that the test method of diversity ensures the accuracy of the test，and the test efficiency has been greatly improved，and it has a good technical development prospects and economic benefits.